Measuring the Success of Activity-Based Costing within the Enterprise Resource Planning Environment in Greek Companies - Kitsantas, Thomas; Stavropoulos, Antonios; Vazakidis, Dimitris (Journal of Accounting, Business and Finance Research, 2021)
Activity-based costing (ABC) is a strategic tool that can enhance all processes and functions of an organization once it is implemented successfully. This study aims to examine ABC implementation success in Greek companies in major sectors of the economy. A web-based questionnaire was conducted between February 2020 and January 2021 to collect data from 102 companies in major sectors of the Greek economy. The success of ABC implementation was assessed across five dimensions: general attitude toward the implementation process, technical and technological characteristics, impact on organizational processes, perceived usefulness in improving job performance, and perceived ease of use. Further, this study compared companies that have fully implemented ABC to those that still practice traditional cost accounting (TCA) by assessing factors that influence ABC success within enterprise resource planning (ERP). Findings from this study show that successful integration of ERP and ABC can minimize operation costs and enhance the competitiveness of the enterprise. In particular, the findings indicate that the degree of ABC within ERP implementation success positively motivates the extent of its use, enhances user performance, increases productivity, and increases user satisfaction with the system. This study contributes to the existing literature since there has been limited research on the measurement of the success of ABC within ERP implementation in Greek companies. It also provides theoretical and practical insights regarding factors that might influence the successful implementation of ABC within ERP that can be applied to other countries. Overall, entities that have implemented ABC have achieved improved outcomes relative to those that still use TCA.